WHY PARENTS ENROL THEIR CHILDREN IN RECREATIONAL GYMNASTICS PROGRAMMES AT THE BEGINNING OF THEIR EDUCATION - Jerneja Fišer Kurnik; Tanja Kajtna; Klemen Bedenik; Marjeta Kovač (Science of Gymnastics Journal)
The purpose of this study was to examine the motives of parents who enrolled their children in recreational gymnastics programmes at six primary schools and their auxiliary branches in the north-east part of Slovenia in the 2007/2008 academic year. The study included 386 parents who (after the programme ended) answered a questionnaire specifically designed for this study. Basic statistical parameters were calculated, and a one-way analysis of variance has been carried out in order to observe the differences in the motives of parents, according to their gender, age, educational level and gender of their child. The results of the study revealed that the most significant motive stated by the parents as a reason for enrolling children in a course was “because sport benefits the health of my child”. This indicates the awareness of parents about the usefulness of sport for the development and health of children. According to gender of parents, there were minor differences found, although differences in the structure of motives were revealed according to the age of parents, their level of education and gender of their child. The prevailing motives of parents indicate that the organisers of gymnastics courses should emphasise such organisation in schools, which will emphasise the effects of exercising on the health of children along with enjoyment and useful spending of free time.